Diversification Des Exportations Et Croissance Économique En Afrique Subsaharienne : Une Analyse En Termes De Sophistication (Global Journal of Human-Social Science, 2020)
In this paper we study the effect of export diversification on GDP per capita growth in Sub-Saharan African countries using GMM, looking in particular at the vertical dimension of the process. We first empirically analyse the simultaneous effet of both horizontal and vertical dimensions of export diversification on economic growth in the per iode 1995-2017. Then we secondly evaluate the specific contribution of the vertical dimension of the process on economic growth. From the empir ical analysis, we show that if both dimensions of export diversification are positively related with growth, only the vertical dimension affect significantly economic growth. However, the impact of manufactured products export ratio in total of merchandise export for the countries which manufactured export exceeds 50% is more important than the others.
Keywords: export diversification; economic growth; dimensions of diversifcation; horizontal dimension; gmm; sub-saharan africa